Reconstructing precipitation in the tropical South Pacific from dinosterol 2H/1H ratios in lake sediment. (15th January 2019) - Maloney, Ashley E.; Nelson, Daniel B.; Richey, Julie N.; Prebble, Matthew; Sear, David A.; Hassall, Jonathan D.; Langdon, Peter G.; Croudace, Ian W.; Zawadzki, Atun; Sachs, Julian P.
Highlights: Sedimentary δ 2 Hdinosterol from 21 freshwater lake core tops on 12 islands. δ 2 Hdinosterol is correlated with δ 2 Hlakewater . δ 2 Hdinosterol is correlated with GPCP mean annual precipitation amount. Fractionation between dinosterol and lake water decreased at the driest lake sites. δ 2 Hdinosterol -GPCP regression supports quantitative precipitation reconstructions. Abstract: The South Pacific Convergence Zone (SPCZ) is the Southern Hemisphere's largest precipitation feature supplying freshwater to 11 million people. Despite its significance, little is known about the location and intensity of SPCZ precipitation prior to instrumental records, hindering attempts to predict precipitation changes in a warming world. Here we use sedimentary molecular fossils to establish a tool for extending the historical record of precipitation. Freshwater lake sediments and water samples were collected from 30 lakes that span a 4.6 mm d −1 range in precipitation rates from the Global Precipitation Climatology Project (GPCP). δ 2 Hlakewater values from 29 lakes ranged from −29 to +23‰ and were inversely correlated ( r  = −0.51, p  < 0.001) with precipitation rates, likely due to the combination of the amount of precipitation plus evaporation. δ 2 H values of the dinoflagellate sterol dinosterol in surficial sediments from 21 lakes ranged from −316‰ in the Solomon Islands to −245‰ in French Polynesia. These δ 2 Hdinosterol values were significantly correlated ( r  = 0.71, p  < 0.001) with δ 2 Hlakewater and inversely correlated ( r  = −0.77, p  < 0.001) with mean annual precipitation rates with a sensitivity of −12.1 ± 2.6‰ (mm d −1 ) −1 . Fractionation between dinosterol and lake water (εdinosterol/lakewater ) decreased at the driest lake sites ( r  =  − 0.70, p  < 0.001). The empirical relationship between δ 2 Hdinosterol and GPCP rainfall, although indirect, provides a means of quantitatively reconstructing past precipitation in the SPCZ region with an uncertainty of less than 3.1 mm d −1, which compares favorably to the 1.5 mm d −1 uncertainty for the satellite-gauge based GPCP precipitation data.